Integrated Planning of Heat Flows in Production Systems - Kurle, Denis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book presents an integrated planning concept for heat flows in production systems comprising various short term and long term related models. Detailed explanations about the modeling and implementation of all relevant system elements such as generic and specific machines types, technical building services (TBS), production planning and control aspects, heat storage units and (waste) heat designs follow. Due to resulting amounts of data, the concept foresees system level appropriate indicators and visualizations for a facilitated evaluation of the model results. An application procedure embeds and describes all models as well. Three exemplary application cases demonstrate the applicability, including the manufacturing of shafts for automotive transmissions, a cooling water system and an academic learning environment.
Introduction -- Heat flows in production systems and its modeling and simulation -- State-of-research -- Concept for an integrated planning of heat flows in production systems -- Exemplary application of concept -- Summary and outlook -- Further exemplary machine type models -- Data tables for the cooling tower(s) model.
Keywords: Industrial engineering; Production engineering; Energy storage; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Industrial and Production Engineering; Mechanical and Thermal Energy Storage; Engineering Thermodynamics, Heat and Mass Transfer